Waiting - Henkes, Kevin (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2015)
Five friends sit happily on a windowsill, waiting for something amazing to happen. The owl is waiting for the moon. The pig is waiting for the rain. The bear is waiting for the wind. The puppy is waiting for the snow. And the rabbit is just looking out the window because he likes to wait! What will happen? Will patience win in the end? Or someday will the friends stop waiting and do something unexpected?
Ages 4-8.
Preschool.
Caldecott Honor, 2016
Keywords: Waiting (Philosophy) -- Juvenile fiction; Animals -- Juvenile fiction; Toys -- Juvenile fiction; Weather -- Juvenile fiction; Waiting (Philosophy) -- Fiction; Animals -- Fiction; Picture books for children